Exploring the role of mitochondrial metabolism and immune infiltration in myocardial infarction: novel insights from bioinformatics and experimental validation - Hou, Jingyi; Wang, Lihan; Zhu, Naiqiang; Li, Xueli (Frontiers in Immunology, 2025)
BackgroundMitochondrial metabolism and immune inflammation play pivotal roles in the MI pathogenesis of myocardial infarction (MI); however, their interplay remains unclear. This study aimed to clarify the roles of mitochondrial metabolism and immune infiltration in MI, using a combination of bioinformatics analyses and experimental validation.MethodsMI chip data (GSE96561, GSE181872, and GSE183272) were obtained from the Gene Expression Omnibus (GEO) database, and mitochondrial gene data were sourced from the MitoCarta3.0 database. Differentially expressed genes (DEGs) were identified and subjected to functional enrichment analyses. Mitochondria-related DEGs (mitoDEGs) were determined by intersecting DEGs with mitochondrial genes and associated Gene Ontology (GO) terms were analyzed using the Metascape database. A protein-protein interaction (PPI) network of mitoDEGs was constructed, and hub mitoDEGs associated with MI were identified using CytoHubba and molecular complex detection (MCODE) algorithms. Transcription factor (TF) and microRNA (miRNA) targets of hub mitoDEGs were predicted using iRegulon and miRWalk plug-ins, respectively, and a regulatory network involving TFs, hub mitoDEGs, and miRNA was established. Immune infiltration in MI was analyzed using ImmuCellAI, and the relationship between hub mitoDEGs and immune infiltration abundance was assessed using the Spearman method. Experimental validation of hub mitoDEGs, immune cell markers (F4/80, CD163 and CD86), and apoptosis-related proteins (BAX/BCL-2 and cleaved caspase-3) was conducted in MI mice, and the association with cardiac function was explored.ResultsMitoDEGs in the MI group were significantly enriched in pathways related to mitochondrial transport and gene expression. Nine hub mitoDEGs closely associated with MI were identified. Immune analysis revealed increased infiltration of mast and plasma cells infiltration and decreased CD4 T cell infiltration in the MI immune microenvironment. Spearman analysis showed positive correlations between hub mitoDEGs and M1 macrophages, Th2 Cells, and monocytes and negative correlations with eosinophils and activated T cells. In MI mice, expression trends of four hub MitoDEGs (Cox5b, Ndufa2, Ndufs6, and Uqcr11) were consistent with the bioinformatics results, and their downregulation was associated with reduced cardiac function. CD86 and apoptosis-related proteins (BAX/BCL-2 and cleaved caspase-3) were markedly elevated in MI groups.ConclusionThese findings suggest that Cox5b, Ndufa2, Ndufs6, and Uqcr11 act as core regulatory molecules in immunometabolism during MI, providing new insights into its pathogenesis and diagnosis.